Study of sugar cane bagasse termotreated biomass for energy purposes - Santos, Juliana Rodrigues Siviero dos; Brito, José Otávio (Revista Hipótese, 2022)
The objective of this study was to analyze the effect of the heat treatment application in sugar cane bagasse in order to improve its features to use as fuel. The biomasses were subjected to laboratory heat treatments comprising temperatures of 250 and 280°C during 0,5 and 2,0 hours. After that, the original and treated biomasses were subjected to laboratory tests including: chemical composition (lignin and extractives), immediate composition by determining the levels of volatiles, fixed carbon and ash and calorific value. The results show that there is an influence of temperature on the yields of biomass analyzed. In general, the higher the temperature of the heat treatment, the lower the yield obtained and, consequently, the greater the loss of mass. There was an increase in fixed carbon content, reduction of volatile matter content and increase in ash content. It was observed that the increase in the heat treatment intensity caused a tendency to increase the lignin content of the material.
Keywords: Termotreatment; Renewable Energy; Bagasse